Desenvolvimento de jogos Action RPG para dispositivos moveis utilizando a engine Godot: um estudo aplicado - Bresolino, Lucas Calado (2025)
The development of independent games for mobile devices is becoming increasingly popular, driven by growing public demand and technological developments. In this context, choosing the right game engine is crucial to the success of the project. Godot Engine is a free and open-source tool that stands out as an economical and simplified option for independent developers and small studios. With an active community and beginner-friendly content, Godot offers a complete development environment that supports everything from creating animations to implementing complex game mechanics. The engine’s flexibility to export to various platforms such as Windows, macOS, Linux, Android, iOS and the Web makes it a versatile choice for projects of different sizes. This work identified the main attractions of Godot Engine and demonstrated its potential for developing Action RPG games for mobile devices by creating a prototype of a medieval game. The engine met all the objectives of the game, which became functional from the first lines of code.